Analysis of The Use Of Ethnobotany-Based Storybooks to Improve Science Literacy in Alpha Generation Children - Syarifah Halifah; Novia Anugrah; Afifa Tiariyanti (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the use of ethnobotanical storybooks as a learning medium in introducing science literacy to early childhood in Enrekang Regency, with a focus on presenting the local plant Pulu Mandoti, which is part of the local wisdom in the Alla Subdistrict Village. The approach was descriptive qualitative, with data collection techniques in questionnaires and interviews with 14 respondents from early childhood education environments in Enrekang Regency. The results showed that 90% of respondents considered the introduction of local wisdom important, especially in planting and caring for Pulu Mandoti plants. Regarding media format, 42% of teachers chose short animated videos, while 50% preferred printed picture storybooks as the most effective medium. Based on these results, this study recommends using ethnobotany-based storybooks in the PAUD curriculum to improve science literacy and introduce local cultural values. Combining picture books and short animations is expected to enrich children's learning experiences, enhance their understanding of science, and foster an appreciation for cultural and natural wealth.